Cardiovascular Pathophysiology for Pre-Clinical Students - Binks, Andrew (Open textbook library., 2022)
Cardiovascular Pathophysiology for Pre-Clinical Students, is an undergraduate medical-level resource for foundational knowledge of common cardiovascular diseases, disorders and pathologies. This text is designed for a course pre-clinical undergraduate medical curriculum and it is aligned to USMLE(r) (United States Medical Licensing Examination) content guidelines. The text is meant to provide the essential information from these content areas in a concise format that would allow learner preparation to engage in an active classroom. Clinical correlates and additional application of content is intended to be provided in the classroom experience. The text assumes that the students will have an understanding of basic cardiovascular physiology that will be helpful to understand the content presented here. This resource should be assistive to the learner later in medical school and for exam preparation given the material is presented in a succinct manner, with a focus on high-yield concepts. Instructors interested in reviewing, adopting, or adapting parts or the whole of the text are requested to register their interest at: https://bit.ly/interest-preclinical.